Determinan yang Memengaruhi Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Bali - I Gusti Ayu Lidya Sriwahyuni; Made Kembar Sri Budhi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Economic growth is used as a benchmark of economic performance that can create increased income and welfare for the community over a certain period. An increase in Gross Regional Domestic Product (GRDP) is commonly used to measure economic growth within a region. This study aims to analyze the influence of investment, labor, district minimum wages, and regional spending on economic growth. The locations used in this study were all regencies and cities in Bali Province during the period 2017–2024. The analysis technique employed was panel data regression with a total of 72 observations. The results indicate that investment has a positive but insignificant effect on economic growth, labor has a positive and significant effect on economic growth, district minimum wages have no significant effect on economic growth, and regional spending has a positive and significant effect on economic growth. These findings suggest that labor absorption and effective regional spending play important roles in encouraging economic growth, while investment and minimum wage policies require further optimization to generate a stronger impact on regional economic development.